A Comprehensive Review on Data Science Frameworks for Big Data Analytics - Hassan Raza; Tsendayush Erdenetsogt; A Singh; Mazhar Farooq; Muhammad Mohsin Kabeer; Muhammad Shahrukh Aslam (PERFECT: Journal of Smart Algorithms, 2026)
The importance of big data analytics is now essential in deriving insights in large and complex information in various industries. This review discusses major data science frameworks, such as Apache Hadoop, Spark, Flink, and Storm, their architecture, capabilities, and a relative advantage of processing batches and in real-time. It also presents major challenges that can affect the framework efficiency, including scalability, latency, and heterogeneity of data, security, and the complexity of operational, among others. Lastly, the new trends such as the adoption of AI, cloud-native architecture, real-time streaming, and intelligent automation are discussed to demonstrate the changing environment. This review gives an in-depth insight into the concept of big data frameworks and how they facilitate the achievement of effective analytics.